2018
DOI: 10.1002/jcp.27984
|View full text |Cite
|
Sign up to set email alerts
|

HER2+ mCRC patients with exon 20 R784G substitution mutation do not respond to the cetuximab therapy

Abstract: The human epidermal growth factor 2 (HER2) gene undergoes various mutations that could alter its activity or respond to the antibody therapies. Cetuximab, a known anti‐EGFR monoclonal antibody (mAB), is widely administered in metastatic colorectal cancer (mCRC) cases. Here we identified mCRC patients who did not respond to cetuximab (500 mg/m2, q2w) after fluoropyrimidine/oxaliplatin regimen failure. Tumor samples were examined with immunohistochemistry for protein distribution, polymerase chain reaction (PCR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Patients with the HER2 L755S mutation were resistant to trastuzumab and lapatinib treatment, and a non-small cell lung cancer patient with HER2 N813D mutations was resistant to afatinib [61,62]. HER2 positive metastatic colorectal cancer patients with HER2 T784G mutation did not respond to cetuximab therapy [63]. A recent study showed that cells with the HER2 L755S mutation were resistant to lapatinib [64].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with the HER2 L755S mutation were resistant to trastuzumab and lapatinib treatment, and a non-small cell lung cancer patient with HER2 N813D mutations was resistant to afatinib [61,62]. HER2 positive metastatic colorectal cancer patients with HER2 T784G mutation did not respond to cetuximab therapy [63]. A recent study showed that cells with the HER2 L755S mutation were resistant to lapatinib [64].…”
Section: Discussionmentioning
confidence: 99%
“…Although most HER2-based studies have primarily focused on breast cancer, the role of this receptor in mCRC has recently been described[ 63 , 64 ]. Previous in vitro and prospective patient studies have suggested that both the presence of mutations related to the active site of the receptor and HER2 amplification are associated with a poor response to anti-EGFR therapy[ 62 , 63 , 65 ]. In addition, the acquisition of mutations in HER2 may be an underlying mechanism of secondary resistance that can be detected early using liquid biopsy.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The HERACLES trials showed that ERBB2 inhibitors are an emerging treatment option in CRC [ 117 ]. It has been described that high ERBB2 expression levels detected by immunohistochemistry were associated with cetuximab resistance in metastatic CRC and that the presence of the R784G mutation, which lies within the protein kinase domain of the protein, correlated with lower survival rate [ 118 ].…”
Section: Changes In Drug Targets (Moc-3)mentioning
confidence: 99%